Encyclopedic learners' dictionaries : a study of their design features from the user perspective - Stark, M. P. (Martin P.) (Lexicographica. Series Maior, 1999)
The series features monographs and edited volumes on the topics of lexicography and meta-lexicography. Works from the broader domain of lexicology are also included if they strengthen the theoretical, methodological and empirical basis of lexicography and meta-lexicography. Thevolumes focus on aspects of lexicography such as micro- and macrostructure, typology, history of the discipline, and application-oriented lexicographical documentation.